2004
DOI: 10.1017/s0025100304001719
|View full text |Cite
|
Sign up to set email alerts
|

VC vs. CV syllables: a comparison of Aboriginal languages with English

Abstract: Traditionally, phonological theory has held that the CV syllable is the basic syllable type across the world's languages. Recently however, Breen & Pensalfini (1999) have challenged the primacy of the CV syllable in phonological theory with data from Arrernte, an Aboriginal language spoken in central Australia. In this study, we set out to see if there is any acoustic phonetic basis to Breen & Pensalfini's claim. We examine real-word data from one speaker of Arrernte, five speakers of English, and three speake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 30 publications
5
36
0
Order By: Relevance
“…Most LE studies of Australian languages have been conducted by Tabain and colleagues (e.g., Tabain and Butcher, 1999). The findings for these languages can be summarized as follows: velar LE slopes are known to exceed 1 for these languages and bilabial slopes are also rather high, while palatal slopes tend to be relatively low (Arrernte, Yanyuwa, and Yindjibarndi: Tabain and Butcher, 1999;Tabain et al, 2004).…”
Section: Locus Equation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Most LE studies of Australian languages have been conducted by Tabain and colleagues (e.g., Tabain and Butcher, 1999). The findings for these languages can be summarized as follows: velar LE slopes are known to exceed 1 for these languages and bilabial slopes are also rather high, while palatal slopes tend to be relatively low (Arrernte, Yanyuwa, and Yindjibarndi: Tabain and Butcher, 1999;Tabain et al, 2004).…”
Section: Locus Equation Analysismentioning
confidence: 99%
“…Previous research conducted by Tabain et al (2004) on Australian languages, specifically, Arrernte, Yanyuwa, and Yindjibarndi (also spelled "Yintjiparnti"), has suggested that magnitudes of consonantal coarticulation by preceding and following vowels tend to be similar in these languages, which have multiple (coronal) places of articulation contrasts (see Sec. I C).…”
Section: B Goals Of Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The Pitjantjatjara recordings were used for , 2015a, 2015b and Tabain, Fletcher, and Butcher (2014). The English recordings were used for Tabain, Breen, and Butcher (2004), as was one of the Arrernte recordings. Many of the Arrernte recordings were used for Tabain and Breen (2011).…”
Section: Stimuli and Measuresmentioning
confidence: 99%
“…Examples in the text can be seen in the transcription of mpwaremere in line 3 of the orthographic version, nhenhe, rekamparre and wernetyeke in line 4, and some others. It surfaces also as a result of certain morphological processes; see table 1 of Tabain et al (2004) for examples. It is by far the most common vowel.…”
mentioning
confidence: 99%